Do influence Nearctic migratory birds in the seasonal pattern of coastal wetlands birds? - García-Olaechea, Álvaro Gonzalo (2018)
If the spring-summer arrival of migratory Nearctic waders influences the increase in richness and abundance of bird assemblages in coastal wetlands then both the richness and abundance of this group of birds will decline by the fall. To verify this, the San Pedro de Vice mangrove was used as a model of study where it was established that the fall in bird species in autumn could be due to the return of migratory species to the northern hemisphere. Therefore, the objective was to determine the decrease in richness and abundance of migratory Nearctic waders. Ten biweekly surveys were conducted between December 2010 and April 2011, covering a distance of 4.5 km from the north of the tidal channel, preferably when the tide was descending. The decrease in richness was analyzed with a Poisson regression, the decrease in abundance was done through the abundance mean with a generalized linear model. There were 19 species of waders considered as migratory Nearctic. Species richness and abundance showed a statistically significant decrease according to the confidence intervals of the respective slopes. It is concluded that migratory Nearctic wader influence the seasonal patterns of bird assemblages in coastal wetlands in Peru.